Cyclic behaviour of steel irregular tubular column panel zones. (September 2020) - Sui, Weining; Zhang, Qiang; Wang, Zhanfei
Abstract: The shear strength, shear distortion, failure mode, and energy absorption performance of irregular circular and box-shaped tubular column panel zones (PZs) were investigated using experimental and analytical methods on the seven steel frame structures. The main parameters include the beam height ratio of left and right beams, the column cross-section, and the configuration of external diaphragm. The key variable, beam height ratio, can affect the PZ shear strength and energy absorption, but has little influence on the initial stiffness of the PZ; the PZ, PZ1, and PZ2, absorb energy together in the initial loading stages, as the load increases, most of the energy begins to be absorbed only by PZ1 which has the same height as the smaller beam, therefore, the design considering only PZ1 is incomplete; excessive PZ shear deformation can cause cracking of the weld root which adversely affects the structure; the configuration of external diaphragm should avoid stress concentration which can cause cracking of the base metal. The chosen analysis methods are capable of simulating the shear strength and failure modes of the PZ obtained in experimental results with acceptable accuracy. Highlights: The reduction in beam height ratio results in a reduction in the load carrying capacity and energy absorption capacity. The design height of the irregular panel zone is between the higher beam and the shorter beam. Excessive shear deformation of the panel zone is detrimental to welded connections with lower toughness.